Perlindungan Hak Ekonomi Fan-Artist Atas Fan-Art dan Fan Merchandise Genshin Impact Sebagai Karya Derivatif dalam Hukum Hak Cipta - Cahyanti, Laudita (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
These days, with the rapid development of technology, there are many games that are created in various media, one of which is on smartphones. Genshin Impact, is one of the most popular game titles in smartphone media, which counts 64 million active players who are still playing this mobile online game. The number of active players in Genshin Impact has led various players to create fan-art and fan-merchandise related to Genshin Impact. The problem is that it is not uncommon for fan-art and fan-merchandise works that have been created by fan-artists to be reprinted by irresponsible people and sold to reap the personal benefits of these people without fan-artist permission. In connection with this, there are questions about how the position of fan-artists as creators of fan-art and fan-merchandise from Genshin Impact in copyright law and how the protection of economic rights of creators of fan-art and fan-merchandise Genshin Impact in copyright law in Indonesia. This research is conducted by doctrinal research method, which is carried out by examining secondary data which includes primary legal materials, secondary legal materials and tertiary legal materials and will only analyze legal products.